2013
DOI: 10.1371/journal.pone.0076521
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Selection on S. aureus between Antimicrobial Peptides and Common Antibiotics

Abstract: With a diminishing number of effective antibiotics, there has been interest in developing antimicrobial peptides (AMPs) as drugs. However, any new drug faces potential bacterial resistance evolution. Here, we experimentally compare resistance evolution in Staphylococcus aureus selected by three AMPs (from mammals, amphibians and insects), a combination of two AMPs, and two antibiotics: the powerful last-resort vancomycin and the classic streptomycin. We find that resistance evolves readily against single AMPs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
67
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 64 publications
(74 citation statements)
references
References 28 publications
4
67
0
3
Order By: Relevance
“…Strains were isolated from populations which were created by selecting S. aureus JLA513 9 (hlalacZ hla+, derived from SH1000, from Simon Foster, University of Sheffield) for 28 days with increasing concentrations of AMPs or with the aminoglycoside antibiotic streptomycin 6 . Streptomycin-selected strains are included here as a positive control since the genetic basis of streptomycin resistance is well-characterized in S. aureus.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Strains were isolated from populations which were created by selecting S. aureus JLA513 9 (hlalacZ hla+, derived from SH1000, from Simon Foster, University of Sheffield) for 28 days with increasing concentrations of AMPs or with the aminoglycoside antibiotic streptomycin 6 . Streptomycin-selected strains are included here as a positive control since the genetic basis of streptomycin resistance is well-characterized in S. aureus.…”
Section: Methodsmentioning
confidence: 99%
“…The concentrations of the selective agents were doubled each week for a total of four weeks. See Dobson et al 2013 Table S1 for full details and precise concentrations 6 . Strains were isolated from each of three independently selected replicate populations per selective agent (with the exception of iseganan-selected populations where only 2 frozen population stocks remained viable), as well as from unselected controls and the ancestral strain JLA513.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, experimental evolution studies have repeatedly shown that AMP resistance evolves readily in vitro [105,106]. Interestingly, the evolution of resistance to AMPs seems more difficult if these are acting in combination, that is, in synergy as discussed above [107]. However, this finding deserves more attention.…”
Section: Introductionmentioning
confidence: 96%